1985
DOI: 10.1159/000171705
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Perforated Gastric Cancer

Abstract: Perforation of the stomach is the most uncommon complication of cancer of the stomach and was found in 9 of 1,620 patients treated over a 23-year period. The 5-year survival rate of 62.8% indicates that aggressive surgical treatment should be applied where possible. In some patients, radical resection is performed as a second procedure after recovery from the acute episode of perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, viable free cancer cells have not been demonstrated in the peritoneal cavity of patients with perforated gastric cancer and the metastatic efficiency of gastric cancer cells possibly shed during perforation is uncertain in the presence of the peritonitis; different studies, included the present one, report of long-term survivors[ 19 ]. When a curative operation can be performed, survival rates after gastric cancer perforation[ 1 , 20 ] appear similar to survival rates observed in elective patients[ 21 , 22 ]. Moreover, Gertsch et al demonstrated how the only factor predicting long term survival is the TNM stage, while age or the size, the location, the depth of infiltration and the histologic grading of the tumor or a delay in treatment after perforation showed no correlation with long-term survival[ 10 ].…”
Section: Discussionmentioning
confidence: 98%
“…However, viable free cancer cells have not been demonstrated in the peritoneal cavity of patients with perforated gastric cancer and the metastatic efficiency of gastric cancer cells possibly shed during perforation is uncertain in the presence of the peritonitis; different studies, included the present one, report of long-term survivors[ 19 ]. When a curative operation can be performed, survival rates after gastric cancer perforation[ 1 , 20 ] appear similar to survival rates observed in elective patients[ 21 , 22 ]. Moreover, Gertsch et al demonstrated how the only factor predicting long term survival is the TNM stage, while age or the size, the location, the depth of infiltration and the histologic grading of the tumor or a delay in treatment after perforation showed no correlation with long-term survival[ 10 ].…”
Section: Discussionmentioning
confidence: 98%
“…10 Perforation of gastric cancer does not preclude long-term survival per se in a substantial number of patients. 5,6 In patients who underwent curative resection survival rate is influenced by the stage of the disease and it is similar to those without perforation and underwent elective surgery. 10,17 Lee et al found that potentially curative resection; TNM stage, and the absence of postoperative complications are the important factors associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…When a gastric perforation is encountered during laparotomy, malignant perforation should be suspected as 10-16% of gastric perforation is caused by gastric cancer. 3,5,6 In presence of diffuse peritonitis intraoperative diagnosis of the cancer is often difficult particularly when frozen section evaluation is not available. Peritoneal seedlings and clinical staging may be misinterpreted due to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Such emergencies are rare in Japanese patients because most Japanese patients have their cancer detected at an of early stage. Perforation has been widely reported to occur in 0.56 to 3.9% of all cases of gastric cancer [1][2][3][4][5], and major bleeding has been reported to occur in as many as 5% of patients [6][7][8]. These emergencies are also rare in the West, and have been described in only a small number of reports in the English literature over the past 20 years [1][2][3][4][5]9].…”
mentioning
confidence: 99%